Fuel Subsidy Removal and Tourist Behaviour in River Ethiope, Nigeria - Ozighi, Anthonia Oke; Awaritefe, D. O. (Universitas Indonesia Mandiri, 2026)
This study examined the impact of Nigeria’s fuel subsidy removal on tourist behavior in River Ethiope, Abraka, Delta State. It investigated how subsidy removal affected travel mode, cost, frequency, demand for tourism products and services, and overall visitor satisfaction. Using a survey and a combination of simple and systematic random sampling, data were collected from tourism visitors. Three hypotheses tested via regression analysis all revealed significant relationships between fuel subsidy removal and tourists’ travel behavior, product/service demand, and satisfaction. The findings indicate that fuel subsidy removal substantially influences tourism patterns in the Abraka region. The study concluded that there is a significant relationship between fuel subsidy removal and the overall satisfaction of tourism visitors in demand for tourism products and services along the River Ethiope region. It recommended, among others, the improvement of coordination among tourism agencies, government financial support for operators, promotion of sustainable tourism, and enhancement of public transport to mitigate subsidy removal effects and improve visitor experiences.